Geothermal driven micro-CCHP for domestic application – Exergy, economic and sustainability analysis. (15th September 2020) - Nami, Hossein; Anvari-Moghaddam, Amjad
Abstract: Geothermal energy is going to play a key role in future smart energy systems. Geothermal-driven domestic energy systems, specifically, will largely contribute to the baseload supply of heating and cooling demand of societies. A low-temperature geothermal resource is considered to drive a domestic-scaled multi-generation system supplying power, heating, and cooling. The proposed cogeneration system includes a small-scale organic Rankine cycle (ORC), a single effect LiBr–H2 O absorption chiller, and heat exchangers to supply domestic space heating and hot water. The waste heat of the ORC is harvested, also, to be used in space heating. Energy, exergy, economic, and sustainability principles are applied to the system to evaluate the system thermodynamic and thermos-economic performance. Results associated with the exergy destruction are obtained and effects on the system performance of chiller supply are investigated. Besides, the thermodynamic performance of the system is evaluated under the summertime and wintertime conditions. Under the base condition, the generator employed in the absorption chiller is found to be the most exergy destructive unit followed by the evaporator utilized in the ORC. Furthermore, results revealed that by increasing the chiller supply rate, the system sustainability index enhances from 1.6 to 2.5 while the system's first law efficiency reduces. Highlights: Utilization of a geothermal source to develop a CCHP is proposed. The aim is to supply energy demand of a neighborhood in terms of power, heating, and cooling. The combined configuration is designed and analyzed thermodynamically and economically. The exergy efficiency may increase up to 49.6% via the proposed integrated system.